CDC Grand Rounds: Improving medication adherence for chronic disease management — Innovations and opportunities. Issue 2 (30th January 2018) - Neiman, Andrea B.; Ruppar, Todd; Ho, Michael; Garber, Larry; Weidle, Paul J.; Hong, Yuling; George, Mary G.; Thorpe, Phoebe G.
Abstract : This article reviews interventions to improve adherence to medications in individuals with chronic medical issues, such as those seen in transplantation.